D-lactate production from Spirulina (Arthrospira platensis) biomass using lactogenic Escherichia coli. (December 2020) - Werlang, Eliana Betina; Ibarra, Estefanía Sierra; Neves, Fabio de Farias; Julich, Jennifer; Martinez, Alfredo; Schneider, Rosana de Cassia de Souza
Abstract: Biomass of Arthrospira platensis was investigated as a raw material for d -lactic acid (D-LA) production through a sequential saccharification and fermentation process with hydrolases (amylase, glucoamylase, and cellulase) and the lactogenic Escherichia coli strain JU15. The study was performed with an initial 10% load (w/w) of dry A . platensis, containing 35% of total carbohydrate. Enzymatic saccharification was carried out in two steps, first with an α-amylase and glucoamylase blend and then with a cellulase cocktail to release the glucose. After enzymatic saccharification (40 h), approximately 30 g L −1 of glucose were released. These hydrolysates were converted with d -lactogenic E . coli JU15, producing 25.5 g L −1 d -lactate, which reached 86% of the theoretical conversion of glucose to lactate after only 9 h of fermentation and 0.255 gD-LA g −1 of dried A . platensis biomass. Graphical abstract: Unlabelled Image Highlights: Arthrospira platensis biomass as substrate to lactate production. Metabolically engineered Escherichia coli JU15 as lactate producer. Fast fermentation of Arthrospira platensis biomass to lactate production.